RANCANGAN MEDIA PEMBELAJARAN BERUPA APLIKASI AUGMENTED REALITY BERBASIS ANDROID - M. Adlan Al Hawari Nasution; Siswanto Siswanto; Eko Suryana (Jurnal Media Infotama, 2023)
Abstract-Augmented Reality (AR) is a technology that combines objects from the real world and virtual objects in real-time conditions. The merging of real and virtual objects occurs with the support of the right technology while the interactions that are carried out can occur using certain devices. AR is a breakthrough in the field of very sophisticated technology. Because with this technology we can make all abstract or virtual things look real or real. So that researchers apply the Waterfall Media AR Mobile Learning Method to be able to display 3D images and animations in class VIII math subjects, specifically geometric shapes including: blocks, balls, cones, cubes, pyramids, prisms, and tubes, Provides convenience for teachers to add insight into the use of AR learning media in increasing student motivation and interest in learning at SMP NEGERI 1 Bengkulu City. Provides convenience for teachers to add insight into the use of AR learning media in increasing student motivation and interest in learning at SMP NEGERI 1 Bengkulu City. Based on the results of testing the learning media application in the form of Android-based Augmented Reality application as expected based on the menu being tested.